OPTIMISASI PARAMETER MESIN PERAJANG UMBI PORANG TERHADAP HASIL KUALITAS POTONGAN CHIPS PORANG DENGAN METODE TAGUCHI - Eli Novita Sari; Dian Ridlo Pamuji; Anggoro Bayu Wicaksono; Akhmad Afandi; M Fauzi Soulton; Syamsul Arifin; Bagiyo Herwono; Nuraini Lusi (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2026)
Porang tubers (Amorphophallus muelleri) have great potential as a food and health ingredient, but improper processing can reduce product quality. One important process is slicing the tubers to produce chips with uniform thickness. This study aims to optimize the parameters of a porang tuber slicing machine using the Taguchi method. The factors tested include the number of blades (2 and 4), the angle of the blades (10° and 15°), and the engine speed (600 rpm and 1200 rpm). The test results showed that the chip thickness was significantly influenced by these three factors. Signal-to-noise (S/N) ratio analysis and analysis of variance (ANOVA) showed that the blade angle contributed the most to the cutting results, namely 70.87%, followed by the number of blades 25.26%, and the engine speed 2.50%. The optimal parameter combination obtained was four blades, a 10° angle, and 1200 rpm, which resulted in an average thickness of 3.11 mm, in accordance with the standard for porang chips (2–8 mm). These results prove that the Taguchi method is effective for optimizing the parameters of the porang tuber chopping machine to improve the quality of the chopped results.